2021
DOI: 10.1111/clr.13730
|View full text |Cite
|
Sign up to set email alerts
|

Interproximal open contacts between implant restorations and adjacent natural teeth as a risk‐indicator for peri‐implant disease—A cross‐sectional study

Abstract: Objectives The primary aim of this study was to investigate the relationship between interproximal open contacts and peri‐implant disease. The secondary aim was to assess patient‐reported outcome measures in relation to contact status. Materials and methods A cross‐sectional study was performed on 61 patients with 142 implants adjacent to at least one natural tooth. Patients underwent a clinical examination to assess contact status and width, plaque index (PI), gingival index (GI), periodontal probing depths (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 35 publications
(43 reference statements)
0
19
0
Order By: Relevance
“…Of 7480 implants, 570 implants were placed in the maxilla and 638 in the mandible. Moreover, while 7 articles 17 , 19 , 20 , 23 , 27 , 29 , 31 included research that was limited to posterior implant-supported prostheses, 3 study 8 , 16 , 34 reported both anterior and posterior implant-supported prostheses, and only one article 26 included anterior prostheses.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Of 7480 implants, 570 implants were placed in the maxilla and 638 in the mandible. Moreover, while 7 articles 17 , 19 , 20 , 23 , 27 , 29 , 31 included research that was limited to posterior implant-supported prostheses, 3 study 8 , 16 , 34 reported both anterior and posterior implant-supported prostheses, and only one article 26 included anterior prostheses.…”
Section: Resultsmentioning
confidence: 99%
“…Fourteen studies 16 , 18 , 23 - 30 , 32 - 34 , 37 were eligible to evaluate the frequency of PCL based on mesial or distal aspects. According to the results, the frequency for the distal aspect was 7.3% (95% CI: 3.7‒14.0%, Q-value=465.431, df=13, P<0.001, I 2 =97.20).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Although the availability of literature is limited, a negative effect of occlusion on dental implant was suggested predominantly in animal studies (47)(48)(49)(50)(51)(52)(53). Similar to natural dentitions (54), open interproximal contact around a dental implant restoration was also associated with a higher probing depth, plaque index scores, and gingival index scores as well as 1.57 times greater risk of developing peri-implant disease (55). Prior to insertion, abutment and restorative complex should be carefully evaluated for any rough surface texture, which might have been developed during its laboratory fabrication.…”
Section: Restorative Considerationsmentioning
confidence: 99%